Estudo da influência do servofreio na sensação de pedal de freio para um veículo comercial de 3,5 toneladas - Jean Cory de Souza Silva (2018)
The present work is a study on the influence of the brake booster and master cylinder assembly on the braking sensation of a commercial vehicle with a gross vehicle weight of 3.5 tons. The braking sensation can be understood as the feeling experienced by the driver from the moment the force is applied to the brake pedal to the total stop of the vehicle or to slow down the speed to a desired level, and encompasses both the comfort and the feeling of safety transmitted to the user. Another term commonly used in this case is the brake pedal feel, which refers more specifically to the relationship between the parameters of the brake pedal, such as pedal force and pedal travel, with the deceleration generated during braking. This study compares the performance of three different brake booster with master cylinder assemblies and was based on an objective evaluation supplemented with a subjective evaluation. The objective evaluation is composed by a mathematical modeling to simulate the braking of the vehicle, model built in a calculation spreadsheet computational program, and by experimental tests. The subjective evaluation was performed with the participation of employees of the vehicle manufacturer, who expressed their opinion about the braking performance of the brake boosters by assigning a rating on a scale of 1 to 10. The comparison of the data obtained in the simulation, in the experimental tests and in the subjective evaluation compose the complete analysis of the brake pedal feel. The results showed that the brake booster and master cylinder parameters can significantly affect the brake pedal feel and that its effects are perceptible to almost all those who drove the vehicles. Among the brake boosters tested, the one that presented shorter pedal travel was pointed as having the best brake pedal feel by 81% of the participants. This study even gives subsidy to new projects, mainly with the use of the simulation model, aiming at shortening time and cost with experimental tests